Contribuições para a micropropagação de Eugenia involucrata DC. e Handroanthus chrysotrichus (Mart. ex DC) Mattos - Paim, Aline Ferreira (2011)
Eugenia involucrata DC. and Handroanthus chrysotrichus (Mart. ex DC) Mattos are native species with economic, ecological and silvicultural. They have problems with their spread via seeds, because they are recalcitrant and lose viability within a few weeks after collection. In addition, there is little information about the propagation of these species. Therefore, the general objective of this study was to evaluate methodologies which may contribute to micropropagation of E. involucrata and H. chrysotrichus. For multiplication of E. involucrata were tested different sources (BAP, KIN, 2iP and TDZ) and concentrations (0, 16 and 32 μM) of cytokinins added to the nutrient medium MS/2. Also, we tested the effect of TDZ (16 or 32 μM) combined with GA3 (0; 10; 20 and 40 μM) added in medium MS/2, on in vitro multiplication of nodal segments. Even for E. involucrata, we examined the effect of NAA (0; 0,5 and 1 μM) combined with TDZ (0; 16 and 32 μM), added to the medium MS/2. Finally, for E. involucrata, we tested the effect of different concentrations of TDZ (0; 16 and 32 μM) added to the nutrient medium MS/2, on the multiplication of shoot apices of seedlings germinated in vitro. For H. chrysotrichus were tested different types of explants (shoot apical segments and epicotyl) and nutrient media (WPM, MS, WPM/2 and MS/2) in the presence and absence of activated charcoal as well as the effect of BAP (0; 2; 4; 8 and 16 μM) on in vitro multiplication of this species. For in vitro multiplication of nodal segments of E. involucrata the cytokinins tested are dispensable; cytokinins favor the growth of bacterial contamination, high levels of contamination reduce in vitro survival and establishment of nodal segments; the in vitro establishment for this species is impaired by the occurrence of leaf chlorosis and swelling of the explants. As for H. chrysotrichus, the shoot apical segments show the highest development in the in vitro survival and establishment than of epicotyl ; there is a high in vitro swelling of the explants in the absence of growth regulators; in the in vitro establishment in medium WPM/2 in the presence of 0,05 μM shoot apical segments are more efficient under low concentrations of BAP; there isgreater calli formation in epicotyl with increase the concentration of BAP, the opposite was true for the shoot apical segment.